2014
DOI: 10.1332/174426413x662806
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge mobilisation in education across Canada: a cross-case analysis of 44 research brokering organisations

Abstract: Knowledge mobilisation (KMb) attempts to address research-policy-practice gaps in education. Research brokering organisations (RBOs) are third party, intermediary organisations whose active role between research producers and users is a catalyst for research use in education. Sample: 44 Canadian RBOs in the education sector. Methodology: employed a new tool to measure KMb efforts of organisations using data from websites. Findings: typology of RBOs (governmental, notfor- profit, for-profit and membership), org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(128 citation statements)
references
References 0 publications
4
116
0
8
Order By: Relevance
“…in action research approaches or quality collaboratives). 129 A recent study, 130 which may be the first to map the work of knowledge brokering organisations, found that the organisations carried out a wide range of brokering functions, including building partnerships, raising awareness, capacity building, implementation support and policy influence. Relational approaches emphasise ongoing, interactive processes of collaboration between research producers and research users around formulation of RQs, production of research evidence and sharing of research findings.…”
Section: Relationship Modelsmentioning
confidence: 99%
“…in action research approaches or quality collaboratives). 129 A recent study, 130 which may be the first to map the work of knowledge brokering organisations, found that the organisations carried out a wide range of brokering functions, including building partnerships, raising awareness, capacity building, implementation support and policy influence. Relational approaches emphasise ongoing, interactive processes of collaboration between research producers and research users around formulation of RQs, production of research evidence and sharing of research findings.…”
Section: Relationship Modelsmentioning
confidence: 99%
“…Or, pour que ces connaissances puissent se traduire par des pratiques plus efficaces et une réussite scolaire rehaussée, encore faut-il qu'il y ait transfert. Des études révèlent pourtant que le transfert des CIR dans les milieux scolaires est des plus complexes et difficiles (Cooper, 2013;Dagenais, Lysenko, Abrami, Bernard, Ramdé et Janosz, 2012;Levin, 2010). Certains dénoncent d'ailleurs l'existence d'un écart important entre les CIR et les pratiques observées en milieu scolaire (Brown, 2012;Davidson et Nowicki, 2012;Lemire, Bigras et Eryasa, 2011).…”
Section: Problématiqueunclassified
“…Pour d'autres encore, les approches de TC prisées au plan organisationnel consistent trop souvent en des gestes et initiatives isolés au lieu de démarches systémiques (Levin et al, 2011;Landry et al, 2008). Des recherches conduites en éducation témoignent en outre de l'importance de l'interactivité dans le TC, de la présence d'échanges formels et informels entre producteurs (ou accompagnateurs) et utilisateurs (Becheikh et al, 2010;Campbell, 2011;Cooper, 2013;Sa, Li et Faubert, 2010).…”
Section: Problématiqueunclassified
See 1 more Smart Citation
“…However, critics from a range of disciplines have questioned the reliability, quality, and ideological foundations of the knowledge produced by the Bank (Banerjee, Deaton, Lustig, Rogoff, & Hsu, 2006;Broad, 2006;Klees, 2008;Torres, 2001;Wilks, 2004). In order to better understand the World Bank's role in the generation and diffusion of knowledge, we adopt the concept of knowledge mobilization, defined as the movement of research from production to dissemination to its ultimate impact on policy and practice (Cooper, 2014).…”
Section: Understanding Knowledge Mobilization and Economic Dominance mentioning
confidence: 99%